A Holistic Approach for an Efficient Day to Day Operation for Blood Bank Market Withdrawals and Recalls Using Departmental Electronic Occurrence System: A CMCVAMC Experience. (9th November 2022) - Patel, S; Patel, V; Petersen, J M; Jhala, D
Abstract: Introduction/Objective: Donor centers and reagent manufacturers may issue recalls or market withdrawals. Donor center withdrawals of blood components involve units that have a reason that may present a risk to the patient, that subsequently require discarding the product if not transfused or appropriate clinical notification and follow-up if already transfused prior to the notification. Reagent recalls involve problems with reagents that require appropriate corrective action as per the circumstances. Patient safety event reporting systems are universal in hospitals and are a backbone of efforts to detect patient safety events and quality problems. Pathology and Laboratory Medicine (P&LMS) at the Corporal Michael J. Crescenz Veteran Affairs Medical Center (CMC VAMC) has established an electronic occurrence reporting (EOR) program to track and respond to these in the blood bank. The authors explored the usefulness of the holistic approach of this initiative. Methods/Case Report: EOR is available to all the employees of Blood Bank in P&LMS, who regularly report all received recalls and market withdrawals into the system. These are reviewed by the supervisor and blood bank medical director and co-director to ensure appropriate steps are taken. Information on all market recalls and withdrawals affecting blood bank were compiled from January 1st, 2021, to June 1st, 2022, for quality assurance review. Results (if a Case Study enter NA): The EOR plays a significant role in organizing the data from all the recalls and market withdrawals to guide improvement in patient care. There were seven market withdrawals during the study period, all from the donor center for blood product component withdrawals. All seven cases were recorded efficiently with review by the blood bank supervisor and blood bank medical director and co-director. Appropriate follow-up action was performed and recorded for all seven cases in the EOR. Conclusion: The EOR for withdrawals recalls in Blood Bank is highly effective, successful program in terms of electronic organized monitoring. This monitoring is part of ensuring quality care in real time, and plays an important role as part of Veteran Affairs position as a High reliability Organization (HRO).